2010
DOI: 10.4071/hitec-dshepherd-tp14
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Au-Au Wire Bonds in Extreme Environments

Abstract: Microelectronics are being required to show high reliability within aero-engines, oil-gas wells and other extreme applications where devices can experience over 250°C, 1000bar, corrosive environments and significant vibration. Currently operation may be only possible for a small number of hours, which necessitates expensive shut-down and replacement. Wire bond interconnects continue to be critical to overall reliability though previous studies have shown that traditional Au-Al bonds fail in such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…For wire bonding, Au bumping of aluminium bond pads with a suitable barrier material to create a monometallic joint between the Au wire and Au bond pad surface is attractive and has been shown to produce stable bonds up to at least 300 o C for 2000 hours [5].…”
Section: Long Term Reliabilitymentioning
confidence: 99%
“…For wire bonding, Au bumping of aluminium bond pads with a suitable barrier material to create a monometallic joint between the Au wire and Au bond pad surface is attractive and has been shown to produce stable bonds up to at least 300 o C for 2000 hours [5].…”
Section: Long Term Reliabilitymentioning
confidence: 99%
“…2 For wire bonding, Au bumping of aluminum bond pads with a barrier material to create a monometallic joint between the Au wire and Au bond pad surface is attractive. Au wire bonding to Au thick film on alumina has been shown to produce stable bonds up to at least 300 C for 2,000 h [6]. There are several options available commercially for the bumping of devices with Au surface metallization, but little work has been undertaken to examine the long-term aging characteristics of Au wire bonds with bumped devices.…”
Section: High Temperature Endurance Studies On Soi Devicesmentioning
confidence: 99%
“…The devices were then Au wire bonded using 25 mm diameter wire using conditions established from previous work [6]. The devices were hermetically sealed using Au-Sn solder between the package seal ring and an Au/Ni plated Kovar lid.…”
Section: A Batch 1: Au/tiw Metallizationmentioning
confidence: 99%
“…Shepherd et al [5] reported small deterioration of the ball shear and wire pull strength after long-term thermal ageing at 250˚C with the ball shear and wire pull strength levels remaining high even after 2000 hours of testing. The low mechanical strength levels resulted from the combined tests in our work indicate the contribution-to-failure of the vibration effects to the temperature related effects.…”
Section: Mechanical Strength Of Bonds and Wiresmentioning
confidence: 99%
“…Furthermore, the bond is not susceptible to interface corrosion or other bonddegrading conditions. Shepherd et al [5] examined the changes in bond mechanical behaviour and the underlying microstructural stability of Au-Au metallurgical systems under 3 thermal ageing at 250˚C and 300˚C. They reported that these systems are mechanically robust in extreme environments with a stable microstructure.…”
Section: Introductionmentioning
confidence: 99%